Studi Pemikiran Pendidikan Islam: Imam Nawawi AL-Bantani - Aidatun Nisrina Nurul Firdaus; Fajarullah Alghifari (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Imam Nawawi AL-Bantani or better known as Syekh NAwawi is a greart cleric from Indonesia of International standard who is the imam at Masjidil Haram. He has a title Al-Bantani because he comes from Banten. He is also an intellectual who has many works such as no les than 115 books concicting of the science of fiqh, monoteisme,tafsir, Sufism, and hadist. Imam Nawawi’s thinking is slaso applied in Indonesia, one of whish is the field of education.